(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
in this article, in the course of scientific work carried out by the researcher and the scientific supervisor, the epidemiology of duodenal ulcer disease in patients with metabolic syndrome in Khorezm region, frequency of occurrence, location of the ulcer, complications with bleeding, statistical analysis, occurrence in relation to gender, district and detection of the disease in the urban area was studied. Archival documents, macro-preparations, and histo-preparations of the last three years were used in the scientific work of the adult department of the Bureau of Pathological Anatomy of Khorezm region.